An Umbrella Review of the Literature on Perinatal Domestic Violence: Prevalence, Risk Factors, Possible Outcomes and Interventions. (July 2023) - Wong, Siu-Ching; Do, Phuc Huyen; Eisner, Manuel; Hughes, Claire; Valdebenito, Sara; Murray, Aja Louise
Perinatal domestic violence (P-DV) is a common form of violence experienced by women and is associated with adverse impacts on their own physical and mental health and that of their offspring. Illuminating the risk factors for, potential effects of, and promising interventions to reduce P-DV is essential for informing policies to tackle P-DV and mitigate its negative impacts. This umbrella review of recent high-quality systematic reviews and meta-analyses of worldwide research on P-DV provides a systematic synthesis of current knowledge relating to the prevalence, risk factors for, possible outcomes of and interventions to reduce and prevent P-DV. 13 reviews identified through systematic searches of computerised databases, manual search and expert consultation met our inclusion criteria (i.e. English systematic reviews and/or meta-analyses that were from recent 10 years, focused on women exposed to P-DV, assessed risk factors, possible outcomes and/or interventions, and were of fair to high methodological quality). Our results suggest that while there is a growing understanding of risk factors and possible outcomes of P-DV, this knowledge has thus far not been translated well into effective interventions. P-DV intervention programmes that have been subject to rigorous evaluation are mostly relatively narrow in scope and could benefit from targeting a wider range of maternal and child wellbeing outcomes, and perpetrator, relationship and community risk factors. The overall quality of the evidence syntheses in this field is reasonable; however, future studies should involve multiple reviewers at all key stages of systematic reviews and meta-analyses to help enhance reliability.